Shape effects of Copper-Oxide (CuO) nanoparticles to determine the heat transfer filled in a partially heated rhombus enclosure: CVFEM approach. (October 2019) - Dogonchi, A.S.; Waqas, M.; Ganji, D.D.
Abstract: In this article, shape effects of copper-Oxide are analyzed for heat transfer characteristics within the partially heated rhombus enclosure. Additionally, a circular barrier is that have three diverse constraints (adiabatic, cold and hot) is placed at the center of the rhombus. Water is used as a base fluid to constitute the working nanofluid ( CuO -water). Heat transfer within the enclosure happens due to a differential temperature at the cavity walls. The governing partial differential equations include conservation of energy, momentum and mass which are numerically solved via CVFEM. The study concludes that heat transfer rate is ascended owing to ascendant in Rayleigh number and descended owing to ascendant in nanoparticles volume fraction. The study further discloses that the maximum heat transfer rate is ascended owing to ascendant in nanoparticles shape factor. In order to determine the stream function and isotherms, various physical domain has been selected for each emerging parameter such as nanoparticles' shape factor, Rayleigh number, and nanoparticle volume fraction. It is concluded that the heat transfer rate is maximum using Platelet shaped nanoparticles.